Penetrating Craniocerebral Injury by the Hook of a School Desk - DAĞÇINAR, ADNAN; ŞİMŞEK, İSMAİL; SAKAR, MUSTAFA; GÜVENÇ, YAHYA (KARGER, 2021)
Introduction: Although penetrating cranial injuries are rare in pediatric patients, these injuries can lead to morbidity and mortality. Removal of a gigantic foreign body from the cranium requires proper management as it has high risk of further brain damage and seizures. Case Presentation: We report the case of a patient with cranial injury caused by hitting the head to the hook of a school desk. Due to the extreme nature of the injury, the following additional steps were necessary: taking help from a local firefighter team to cut the desk, surgical removal of the foreign body, and cranioplasty after 6 months. Following this, he was discharged without neurological deficits. Discussion/Conclusion: Neurotrauma is one of the major causes of death in children. The damage and effect of the injuring foreign body depends on its size, shape, velocity, trajectory, and entry point. It should be kept in mind that any high-frequency processes applied on the extracranial parts of conductive objects, such as metal bars, may trigger seizures. Preoperative extracranial intervention for huge penetrating foreign bodies should be performed under anticonvulsant administration and intubation to decrease the risk of epileptic seizures and its complications.
Keywords: Gigantic foreign body; Seizure; Surgery; Head injury